2022
DOI: 10.1101/2022.03.28.22273040
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exome-wide association study to identify rare variants influencing COVID-19 outcomes: Results from the Host Genetics Initiative

Abstract: Host genetics is a key determinant of COVID-19 outcomes. Previously, the COVID-19 Host Genetics Initiative genome-wide association study used common variants to identify multiple loci associated with COVID-19 outcomes. However, variants with the largest impact on COVID-19 outcomes are expected to be rare in the population. Hence, studying rare variants may provide additional insights into disease susceptibility and pathogenesis, thereby informing therapeutics development. Here, we combined whole-exome and whol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 65 publications
2
8
0
Order By: Relevance
“…Using an unbiased X-wide gene burden test, we also identified X-linked recessive (XR) TLR7 deficiency in 17 male patients aged 7-71 years with critical COVID-19 pneumonia, accounting for ∼1% of cases in men (Figure 1) [28]. Moreover, six of the 11 TLR7 variants previously reported in patients from other studies were deleterious (carried by nine of 16 patients) [2934], whereas the TLR7 variants in other studies were not disclosed [20,21]. TLR3 senses viral dsRNA in respiratory epithelial cells, whereas TLR7 senses ssRNA in plasmacytoid dendritic cells [1].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Using an unbiased X-wide gene burden test, we also identified X-linked recessive (XR) TLR7 deficiency in 17 male patients aged 7-71 years with critical COVID-19 pneumonia, accounting for ∼1% of cases in men (Figure 1) [28]. Moreover, six of the 11 TLR7 variants previously reported in patients from other studies were deleterious (carried by nine of 16 patients) [2934], whereas the TLR7 variants in other studies were not disclosed [20,21]. TLR3 senses viral dsRNA in respiratory epithelial cells, whereas TLR7 senses ssRNA in plasmacytoid dendritic cells [1].…”
Section: Introductionmentioning
confidence: 96%
“…Other children with AR IFNAR1, IFNAR2, TBK1, or STAT2 deficiency were subsequently reported, as well as children with AR TYK2 deficiency [1519] (Figure 1). Some other groups were unable to replicate these findings, but the variants were not tested biochemically and it is unclear whether recessive defects were considered [11,2022]. There may also be other reasons for their findings [1,23], the most important being the age distribution of the case cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, even the most robustly associated and replicated common variants are predicted to modestly increase an individual's risk for severe COVID-19 by a maximum odds ratio (OR) of about 2 [32], as opposed to an estimated OR of 50 for rare variants that cause IEI [48]. Three studies have so far performed large-scale genome-or exome-wide studies that studied associations between rare variants and disease susceptibility in non-hospitalized patients with confirmed SARS-CoV-2 infection compared to population controls [41,49,50]. Only one rare variant upstream of ACE2 was found that reached exome-wide significance, correlating with decreased expression of the SARS-CoV-2 receptor [41].…”
Section: Genetic Associations With Susceptibility To Severe or Critic...mentioning
confidence: 99%
“…Although a relationship between rare variants in these type I IFN genes and critical COVID-19 is plausible given the importance of intact type I IFN signalling in the anti-SARS-CoV-2 host immune response and the corroboration by some additional cases, four larger, independent studies failed to replicate the enrichment of variants in the TLR3 and IRF7-pathway in patients with critical COVID-19 [35,49,50,55]. This discrepancy could be in part explained by differences in cohort characteristics, including age distribution, definition of disease severity and possibly also clinical baseline parameters such as pre-existent comorbidities or history of infections, and the use of a-or pauci-symptomatic versus population controls.…”
Section: Inborn Errors Of Type I Interferon Signalling In Patients Wi...mentioning
confidence: 99%
“…In addition to GWAS and the associated data, TLR7 located in the X chromosome was considered a potential monogenic cause that predisposed young male patients without comorbidities to severe COVID-19 [ 13 , 14 ]. The most recent research from 21 cohorts across 12 countries also reported that rare, deleterious TLR7 variants are risk factors that predisposed the severity of COVID-19 (13.1-fold increase) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%